Consommation de tabac : Facteur de risque pour la consommation de drogues - Farida GUEMAZ; Fayza DJENIDI (Revue des Sciences Humaines, 2015)
This article aims to highlight the role of smoking as a risk factor for the use of drug among adolescents. Since the latter increasingly being perceived by adolescents as  frustrating social codes transgression, there is the desire in it to play with risk, while sucking also to reach through this act to a state of wholeness and self-assertion, from there, his identity  is built, his personality is confirmed; a personality rather suspicious towards adults.